Veterinary Education during Covid-19 and Beyond—Challenges and Mitigating Approaches - Jennifer Routh; Sharmini Julita Paramasivam; Peter Cockcroft; Vishna Devi Nadarajah; Kamalan Jeevaratnam (Animals, 2021)
The public health implications of the Covid-19 pandemic have caused unprecedented and unexpected challenges for veterinary schools worldwide. They are grappling with a wide range of issues to ensure that students can be trained and assessed appropriately, despite the international, national, and local restrictions placed on them. Moving the delivery of knowledge content largely online will have had a positive and/or negative impact on veterinary student learning gain which is yet to be clarified. Workplace learning is particularly problematic in the current climate, which is concerning for graduates who need to develop, and then demonstrate, practical core competences. Means to optimise the learning outcomes in a hybrid model of curriculum delivery are suggested. Specific approaches could include the use of video, group discussion, simulation and role play, peer to peer and interprofessional education.